Changing petroleum engineering education to meet industry demand - Smith, Lisa; Evans, Brian (Australian Petroleum Production and Exploration Association Limited, 2010)
The Department of Petroleum Engineering at Curtin University had its inception in 1998. For the last 10 years,it lectured the Masters in petroleum engineering course to local Australian and international students, graduatingmore than 200 students. The rapid increase in the price of oil during 2006/7 saw a sudden and substantial growthin industry employment opportunities, which resulted in the department losing over half of its staff to industry. At the same time, the supply of local students reduced to less than 10% of those taking the course. This loss in both student numbers and staff at the same time threatened the department’s future, and resulted in the need for a new focus to return the department to stability.A number of new initiatives were introduced, which included: bringing industry into the decision-making processes; introducing a new two-year Masters program to assist high quality migrant students obtain Australian permanent residency; increasing the advertising of petroleum engineering as a career option to schools and industry; linking with UNSW, UWA and Adelaide universities to establish a joint Masters program; introducing a new Bachelor’s degree in petroleum engineering; changing the block form of teaching to a semester-based form; and having the Commonwealth recognise the new Masters program for Commonwealth funding of Australian students as a priority pathway to a career as a petroleum engineer while the Bachelors program gathered momentum. This paper maps the positive changes made during 2008/9, which led to a 100% increase in student numbers, a 50% increase in staff to stabilise teaching, a 400% increase in active PhD students, and industry projects to deliver an increasing stream of high quality, industry-ready, graduate petroleum engineers over the next 10–20 years into the current ageing population where the average age of a petroleum engineer is 51.